Pengaruh Motivasi terhadap Kinerja Pegawai pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Paser - Karlina Karlina; Ainun Ainun; Aris Jaya Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine and analyze motivation towards employee performance at the Community and Village Empowerment Service of Paser Regency. The research design used in this study is a quantitative research design. In this study, the population is employees of the Community and Village Empowerment Service of Paser Regency totaling 69 employees consisting of 29 civil servants and 40 PTT employees. The sampling technique used in this study is using saturated sampling technique so that the number of samples in this study is 69 employees. Data collection techniques are carried out by means of observation and distribution of questionnaires. Researchers use multiple linear regression tools using the SPSS application program. From the results of the study, it is known that the variables that have a significant effect on employee performance (Y) of Employees at the Community and Village Empowerment Service of Paser Regency are intrinsic motivation (X₁), and it is also known that the dominant effect on employee performance (Y) is intrinsic motivation (X₁) with a t-value of 8.321> t-table value of 1.66827 with a significance level of 0.000. The coefficient of determination (R²) value of 0.885 or 88.5% explains that the independent variables of intrinsic motivation (X₁) and extrinsic motivation (X₂) contribute to the influence of the dependent variable of employee performance (Y) of 88.5%, while the remaining 11.5% is influenced by other variables not included in this study.